Predictors of sleepiness in a large-scale epidemiology study ESSE-RF - Bochkarev, Mikhail; Korostovtseva, Lyudmila; Rotar, Oxana; Verbitskaya, Elena; Sviryaev, Yurii; Zhernakova, Yulia; Shalnova, Svetlana; Konradi, Alexandra; Chazova, Irina; Boytsov, Sergey; Shlyakhto, Evgeny (Frontiers in Neurology, 2024)
To identify predictors of excessive daytime sleepiness we analyzed data from the 'Epidemiology of cardiovascular diseases in regions of Russia (ESSE-RF)' study. Methods: Data from participants of the cohort study ESSE-RF (2012-2013), aged 25-64 years, from 13 regions of Russia were analyzed (2012)(2013). The participants were interviewed regarding their sleep complaints. Sleepiness was considered significant if it occurred at least three times a week. The examination encompassed social, demographic, and anthropometric measures, lifestyle factors, self-reported diseases, and laboratory parameters. The final analysis included 13,255 respondents. Results: Frequent (≥3 times/week) sleepiness was reported by 5,8%, and occasional sleepiness (1-2 times/week) by 10.8% of respondents. Multivariate regression analysis identified significant predictors of frequent sleepiness. Sleep complaints (insomnia, sleep apnea, snoring) and frequent use of sleep medication were prominent factors. Additionally, age, female gender, higher education, and retirement status were associated with sleepiness. Beyond demographics and sleep, the analysis revealed predictors: abnormal anxiety levels, low high-density lipoprotein, high salt intake and following medical conditions: arrhythmia, hypertension, myocardial infarction, other heart diseases, and renal disease